Work Motivation in Improving Employee Performance - Arie Yusnelly; Desmawati Desmawati; Nanda Suryadi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This research was conducted at UPT. Population and Civil Registration of Bukit Raya District, Pekanbaru City, while the purpose of this study was to determine the effect of work motivation on employee performance at UPT. Population and Civil Registration of Bukit Raya Pekanbaru City Then the sample in this study were 30 employees at the UPT. Population and Civil Registration of Bukit Raya Pekanbaru City and used as respondents, in this study used a quantitative descriptive analysis using a simple linear regression analysis method using the SPSS Version.22 program. Based on the results of the analysis that has been done, it shows that partially the work motivation variable has a positive and significant effect on employee performance at the UPT. Population and Civil Registration of Bukit Raya Pekanbaru City.